SILATIP Dit Reskrimsus Polda Jateng Unit Cyber Crime Menggunakan Metode Extreme Programming - Fadli Dony Pradana; Much Aziz Muslim (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
The Special Criminal Investigation Directorate is the executing element of the main task under the Regional Police Chief, led by Dir Reskrimsus with the rank of Chief of the Police Commissioner (Kombes Pol) / Echelon II-B, tasked with conducting investigations and investigating special crimes, coordinate, supervise, and administer PPNS investigations in accordance with statutory regulations. So far, the Directorate of Criminal Investigation of the Central Java Regional Police, especially the Cyber Crime Unit, in its service still uses manual methods. This was felt to be inefficient because of the large number of complaints coming in and the lack of police personnel who handled complaints from reporters so that servants to the community were judged to be less than optimal and needed a long time in a complaint report. This study uses the Extreme Programming method in designing the developed system. Based on the analysis and discussion, it can be concluded that Extreme Programming is one method that supports the acceleration of the development of a small to medium scale system and can improve the quality of the system. Unfortunately, Extreme Programming does not have formal documentation so there is no measuring instrument that shows that the system has been completed.